Beneficial effects of Elaeagnus rhamnoides (L.) A. Nelson and its most abundant flavonoids on the main mechanisms related to diabetic bone disease - Roman Biro; Radoslav Omelka; Anna Sarocka; Noemi Penzes; Veronika Kovacova; Vladimira Mondockova; Monika Martiniakova (Pharmaceutical Biology)
Context Diabetes mellitus represents a group of metabolic disorders that can adversely affect numerous organ systems, including the skeletal system. It elevates bone fragility and causes secondary osteoporosis, known as diabetic bone disease (DBD). The treatment of DBD depends on the control of hyperglycemia supplemented with anti-osteoporotic agents, but this has unsatisfactory efficiency.Objective This article provides a comprehensive review on the effects of Elaeagnus rhamnoides (L.) A. Nelson (sea buckthorn; family Elaeagnaceae), a prospective anti-diabetic and osteoprotective supplement, and its most abundant flavonoids (quercetin, isorhamnetin, kaempferol) on major mechanisms related to DBD.Methods ‘Sea buckthorn’ (SB), ‘quercetin’, ‘isorhamnetin’, ‘kaempferol’, ‘DBD’, ‘hyperglycemia’, ‘inflammatory state’, ‘insulin resistance’ (IR), ‘advanced glycation end products’ (AGEs) were used as keywords, and relevant literature was obtained from online databases (PubMed, Web of Science, Scopus).Results and Conclusions SB and flavonoids mentioned above exert hypoglycemic and anti-inflammatory properties, attenuate IR, inhibit AGEs formation, thereby positively affecting the main DBD-related mechanisms. The direct effect of SB on DBD has not been investigated yet, but the beneficial impact of quercetin on DBD has been revealed. Therefore, it can be assumed that SB could favorably influence DBD, as its great potential to treat other bone-related diseases (osteoporosis, rheumatoid arthritis) has been reported. Further research, including high-quality in vitro and animal model studies, as well as large-scale clinical trials, is needed to confirm such a putative positive effect and to identify more efficient therapies against various diabetic complications, including DBD.